KEDUDUKAN WANITA DI IRAN: MENGUNGKAP PANDANGAN ULAMA SY’IAH - M. Sadik (Hunafa: Jurnal Studia Islamika, 2005)
In Iran, woman emancipation does not undergo fundamental change compared with that in other Islamic worlds. In Iran, woman are still in subordinate position. It is within this context that conservative theological thought of  Shi’i ulamas (Islamic scholars), especially Khomeni  gave a great contribution to the subordinating of  status of woman in Iran. This article tries to discuss  status of woman in Iran from Shi’i  ulama’s perspective. Kata Kunci: Kedudukan wanita, ulama Syi’ah